1987
DOI: 10.1002/1097-0142(19870315)59:6<1206::aid-cncr2820590629>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration biopsy in the diagnosis of thyroid cancer and thyroid disease

Abstract: Fine needle aspiration biopsy (FNAB) performed for diffuse and nodular goiter in the past 5 years, was evaluated in 1399 cases. Surgery was performed on the basis of FNAB cytologic diagnosis that was positive or suggestive of malignancy and/or a suggestive clinical history. Surgery also was performed in cases of cold nodules with negative FNAB results that did not respond to 6 months of suppressive thyroxine therapy. A correlation of cytologic findings with histologic findings was possible in 415 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
3
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 10 publications
2
30
3
4
Order By: Relevance
“…In Non-neoplastic lesions, 34 were Nodular colloid/adenomatous goiter, 4 were Hashimoto thyroiditis and 1 thyroiditis. In our study, of the 9 cases of neoplastic lesions, 5 cases were Follicular neoplasm, 4 cases were Papillary carcinoma and 1 was Anaplastic which is similar to the study of Hawkins et al 12 . In the present study, 3 cases of papillary carcinoma on FNA were confirmed by histopathology with and 1 case of Follicular adenoma on FNAC turned out to be follicular variant of papillary carcinoma with a diagnostic accuracy of 66.7% which is comparable with the study of Gupta et al 11 .…”
Section: Table 2 Distribution Of Cases According To Hisopathologicalsupporting
confidence: 90%
“…In Non-neoplastic lesions, 34 were Nodular colloid/adenomatous goiter, 4 were Hashimoto thyroiditis and 1 thyroiditis. In our study, of the 9 cases of neoplastic lesions, 5 cases were Follicular neoplasm, 4 cases were Papillary carcinoma and 1 was Anaplastic which is similar to the study of Hawkins et al 12 . In the present study, 3 cases of papillary carcinoma on FNA were confirmed by histopathology with and 1 case of Follicular adenoma on FNAC turned out to be follicular variant of papillary carcinoma with a diagnostic accuracy of 66.7% which is comparable with the study of Gupta et al 11 .…”
Section: Table 2 Distribution Of Cases According To Hisopathologicalsupporting
confidence: 90%
“…0% false positive rate in our series is also an important point that needs to be emphasized. The false positivity rate reported in the literature is 0% to 2.5% (22). The series by Chao et al (2) provides a rate as high as .4%.…”
Section: Discussionmentioning
confidence: 96%
“…The figure shows the distribution of the peak activities of aminotransferases as determined from the case records (normal range: aspartate aminotransferase 13-42 U/I, alanine aminotransferase 11-50 U/l). The geometric mean of the peak activity of aspartate aminotransferase was 157 U/l for patients who received streptokinase and 120 U/I for those who received placebo (p<005; ratio 1-31, 95% confidence interval 1-02 to 11 AUGUST 1990 having increased activity of i-hydroxybutyrate dehydrogenase.…”
Section: Subjects Methods and Resultsmentioning
confidence: 99%